Edukasi Manajemen Usaha Bagi UMKM Melalui Seminar Manajemen UMKM Desa Penakir - Muhammad Khoirul Fikri; Muhammad Fakhtul Ulum; Muhammad Bagus Setyawan; Maulida Ayu Pangesti; Uvi Syarifah; Rizky Andrean (CV. ALIM'SPUBLISHING, 2024)
This community service aims to provide education and understanding of business management to the community and MSMEs in Penakir Village, Pulosari District, Pemalang Regency, Central Java Province. The method used in this service is through seminar activities to educate the public about MSME management which is delivered orally by the presenters. The results of the seminar activities succeeded in identifying the problems faced by MSMEs and recommending several simple things that they can apply to develop their businesses.